(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the modern world, museums play a key role in the preservation and transfer of the cultural heritage of mankind. This work discusses the importance of museums as cultural institutions, their role in education and entertainment, as well as their impact on tourism and the economy. Various types of museums, their architecture, expositions and technological innovations that contribute to the enrichment of the visitor’s experience are covered. The challenges faced by museums in the modern digital age and the possibilities of modern technologies to overcome them are also considered.